REORIENTASI PENDIDIKAN ISLAM DALAM ERA DIGITAL: TELAAH TEORITIS DAN STUDI LITERATUR - Nasir, Muhammad; Sunardi, Sunardi (Al-Rabwah, 2025)
This article aims to theoretically examine the development and challenges of Islamic education in the digital era and to propose a reconstruction of its paradigm toward a more integrative, transformative, and contextual model. Employing a literature review method, this study analyzes both classical and contemporary works by prominent Islamic education scholars such as al-Attas and al-Faruqi, as well as empirical sources concerning the current state of Islamic education in Indonesia. The findings reveal that Islamic education today faces a crisis of purpose, disciplinary fragmentation, and a weak integration of values within the learning system. Furthermore, epistemic challenges arising from digital disruption and low value literacy among students exacerbate these issues. Therefore, a new paradigm is needed one grounded in the integration of knowledge and faith, the role of teachers as agents of renewal, and the creation of an educational ecosystem that is adaptive to contemporary changes. This article underscores the importance of Islamic education not merely as an instrument for knowledge transmission, but also as a vehicle for civilizational transformation